Groupwork researchers as ‘temporary insiders’ - Doel, Mark; Orchard, Kim (Groupwork, 2012)
This paper aims to build the evidence base for groupwork through an exploration of the potential for participant observation in groups. The value of the participant observation method is considered by presenting the available literature and by analysing its use with a particular group. The group used as a case example is one for parents and carers experiencing difficulties with the behaviour of their adolescent children, and it illustrates both the dilemmas and the opportunities of participant observation. This group’s structure is described in detail to provide the backcloth against which the observation took place and to link the process of participant evaluation with the specific detail of the group programme. The paper develops a variant of the notion of the participant observer, in this case as an active temporary insider in the group, in which the process of independent evaluation by a person external to the group inevitably becomes part of the group process itself. There is discussion of how best to use this characteristic of participant observation, concluding with some guidelines emerging from the research. The guidance is intended to aid temporary insiders to provide independent evaluation and to build the evidence base. The paper is a collaboration between a groupwork academic and a groupwork practitioner.